(untitled) (International Journal of Artificial Intelligence Engineering and Systems, 2026)
The proliferation of diverse 5G services with stringent and heterogeneous quality of service (QoS) requirements has elevated network slicing to a foundational architectural principle. Realizing the full potential of network slicing demands dynamic, automated resource allocation mechanisms that can adapt to rapidly fluctuating traffic and service-level demands across shared physical infrastructures. This paper presents a comprehensive framework for QoS-aware 5G network slicing driven by deep reinforcement learning, specifically leveraging the proximity policy optimization (PPO) algorithm as a central decision-making engine. Departing from conventional optimization or heuristic-based approaches, the framework treats slice resource allocation as a sequential decision-making problem under uncertainty, enabling continuous learning and adaptation in real time. The discussion is oriented toward system-level analysis, examining the architectural decomposition of the framework into monitoring, policy, and orchestration components, and evaluating structural trade-offs among centralization, scalability, and response latency. Critical dimensions such as multi-tenancy governance, sustainability through energy-aware policy shaping, robustness against non-stationary network conditions, and fairness among competing slices are analyzed in depth. Particular attention is given to deployment pragmatics, including the integration with existing software-defined networking and network function virtualization control planes, the role of digital twins for pre-deployment policy validation, and the challenge of maintaining slice isolation under dynamic resource fluctuations. Policy implications are explored with respect to regulatory frameworks for infrastructure sharing and net neutrality, arguing that intelligent resource brokers must be designed to balance commercial incentives with equitable access. The analysis draws on cross-domain insights from cloud orchestration, autonomous systems, and industrial control, positioning the proposed framework as a pathway toward self-optimizing, resilient, and ethically aligned 5G networks. By synthesizing advances in deep reinforcement learning with architectural and governance considerations, the paper contributes a holistic perspective on future-ready slice orchestration.